The role of gibberellin in the reproductive development of Arabidopsis thaliana - Plackett, Andrew R. G. (2012)
The plant hormone gibberellin (GA) promotes several processes during Arabidopsis reproductive development, including the transition to flowering, floral organ growth and fertility. GA functions during stamen development to promote degradation of the tapetum cell layer through programmed cell death (PCD) and in post-anthesis pollen development. Bioactive GA is synthesised through a multi-step pathway, in which the last two biosynthetic steps are expressed as conserved multigene families. One of these, the GA 20-oxidases (GA20ox) consists of five paralogues in Arabidopsis, though physiological functions have only been ascribed to two (AtGA20ox1 and -2). Through a reverse genetics approach, this project demonstrates that AtGA20ox1, -2 and -3 account for almost all GA20ox activity in Arabidopsis, with very little evidence of any functions for AtGA20ox4 or -5. Unlike AtGA20ox1, -2, -3 and -4, AtGA20ox5 possesses only partial GA20ox activity, performing the first two out of three sequential catalytic conversions in vitro.